LESSON LEARNED PENGARUH PEMBELAJARAN ONLINE, PERAN ORANGTUA DAN GURU DALAM MEMOTIVASI BELAJAR SISWA PADA PANDEMI COVID-19 - Mufti Alfarizi; Sukmo (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
In early January 2019, scientists identified a new infectious disease caused by the coronavirus. On March 23, 2020 Indonesia implemented a nationwide closure of schools and universities (Lockdown), which resulted in more than 91% of the world's student population stopping their studies. During this school closure, all face-to-face learning was cancelled, forcing many schools to quickly switch from face-to-face learning to fully online learning. The sudden transition to fully online learning has been stressful for many teachers, parents and students who prefer hands-on instruction. The purpose of this researcher is to analyze lesson learned the influence of online learning, the role of parents and teachers in motivating student learning during the co-19 pandemic. This study used data collection using the survey method, namely by distributing questionnaires online and using the method Structural Equation Model (SEM), where data processing and analysis uses SPSS 24 software with Likert scale measurements (scale 1 to 5) and smartPLS 4. The sample in this study was students aged 17 to 19 years in class 12 high school who studied online during the Covid 19 pandemic The results of this study indicate that the implementation of online learning during the Covid-19 pandemic has various role problems experienced by teachers and parents in motivating learning. The problem from parents is that parents have not been able to meet the urgent needs of their children (Laptops, Internet, cellphones, etc.) for learningonline in the context of a pandemic, while teachers face barriers to interaction and socialization that do not occur in online learning.